Differences in osmotic adjustment, foliar abscisic acid dynamics, and stomatal regulation between an isohydric and anisohydric woody angiosperm during drought. (8th November 2017) - Nolan, Rachael H.; Tarin, Tonantzin; Santini, Nadia S.; McAdam, Scott A.M.; Ruman, Rizwana; Eamus, Derek
Abstract: Species are often classified along a continuum from isohydric to anisohydric, with isohydric species exhibiting tighter regulation of leaf water potential through stomatal closure in response to drought. We investigated plasticity in stomatal regulation in an isohydric ( Eucalyptus camaldulensis ) and an anisohydric ( Acacia aptaneura ) angiosperm species subject to repeated drying cycles. We also assessed foliar abscisic acid (ABA) content dynamics, aboveground/belowground biomass allocation and nonstructural carbohydrates. The anisohydric species exhibited large plasticity in the turgor loss point (ΨTLP ), with plants subject to repeated drying exhibiting lower ΨTLP and correspondingly larger stomatal conductance at low water potential, compared to plants not previously exposed to drought. The anisohydric species exhibited a switch from ABA to water potential‐driven stomatal closure during drought, a response previously only reported for anisohydric gymnosperms. The isohydric species showed little osmotic adjustment, with no evidence of switching to water potential‐driven stomatal closure, but did exhibit increased root:shoot ratios. There were no differences in carbohydrate depletion between species. We conclude that a large range in ΨTLP and biphasic ABA dynamics are indicative of anisohydric species, and these traits are associated with exposure to low minimum foliar water potential, dense sapwood and large resistance to xylem embolism. Abstract : We propose that the turgor loss point and dynamics in foliar ABA levels during drought are key indicators of plant stomatal regulation strategy, that is, isohydry/anisohydry, both within and across species. In a study of potted plants subject to cycles of wetting and drying, we found that, compared to an isohydric species, an anisohydric species (a) exhibited a switch from abscisic acid to water potential‐driven stomatal closure during drought; (b) exhibited a larger decline in the water potential associated with turgor loss; and (c) this resulted in a corresponding increase in stomatal conductance at medium‐to‐low foliar water potentials in plants pre‐exposed to drought. In contrast, (d) the isohydric species relied on foliar ABA alone to close stomata and responded to drought through increased root:shoot ratio, resulting in improved leaf water relations.